Concept Understanding and Causes of Student Misconceptions on Simple Harmonic Motion - Mufit, Fatni; Karzah, Khofifah (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This study aims to evaluate the profile of students' misconceptions and their causes when learning simple harmonic motion. Five tier multiple choice diagnostic test with 20 questions has been for determination of the misconceptions and their causes. The descriptive method with quantitative approach was used in this exploration. There were 177 high school pupils in the sample data collection for this study. This study used the following sample was a purposive sample, that is high level and low level schools based on the average physics exam scores obtained from physics teachers at the high school level. Overall, students' concept getting to know simple harmonic motion material falls into the low category. The greatest concept understanding is found in high-level schools. Students' misconceptions in physics lessons based on simple material on harmonic motion overall fall into the medium category. The largest misunderstanding occur in high-level schools. Students' misconceptions in learning physics on simple harmonic motion material as a whole fall into the medium category. The biggest misconceptions occur in high-level schools. Where the highest misconceptions are highest in the concept of deviation, velocity and acceleration of simple harmonic motion. The more dominant cause of misunderstanding at both school levels is students' personal thoughts, followed by teachers, the internet, books, and friends.